Development of Defect-Rich WO3-x/TiO2 Heterojunction Toward Dual-Functional Enhancement: Boosting SERS and Photocatalytic Performance - Xunfei He; Yinyan Gong; Lengyuan Niu; Can Li (Nanomaterials)
Semiconductors have emerged as promising candidates for surface-enhanced Raman scattering (SERS) applications due to their inexpensiveness and good chemical stability. Nevertheless, their low enhancement ability compared to noble metals makes it desirable to explore strategies for improving SERS performance. Since charge transfer (CT) between semiconductors and analytes plays a crucial role on the chemical enhancement mechanism of SERS, heterojunction engineering, a powerful method to boost optoelectronic performance via tailoring interfacial charge transfer, provides a promising approach. Here, we prepared defect-rich WO3-x/TiO2 nanocomposites via a facile solvothermal method to achieve dual-functional enhancement in SERS and photocatalytic activity. Due to suppressed recombination of charge carriers in WO3-x/TiO2 heterojunction with type II band alignment, more photogenerated carriers are available for CT, consequently increasing molecular polarizability. The SERS intensity of WO3-x/TiO2 is at least three times that of its component semiconductors, with a detection limit of 10−10 M for methyl orange (MO). Meanwhile, the suppressed recombination of charge carriers also results in higher degradation efficiency of WO3-x/TiO2 heterojunction (93%) than WO3-x (47%) and TiO2 (54%) under visible-light irradiation for 120 min. This work provides insightful information on the development of dual-functional semiconductor systems through band structure engineering for ultrasensitive sensing and efficient remediation of environmental pollutants.